Application The Principle of Pacta Sunt Servanda In Consumer Protection Indonesia - Aliya Sandra Dewi (Journal of Mandalika Literature, 2025)
An agreement is part of a contract that has legal consequences and is binding on the parties involved and also in the implementation of the existing agreement related to the law of property that is bound by the agreement that has been agreed upon. The agreement in question has met both formal and material requirements and if it is associated with consumer protection, the agreement of pacta sunt servanda in trading goods and/or services must bind and be bound by the agreement that has been made and not violate rights either intentionally or negligently. What has been agreed upon in the agreement usually concerns the costs that must be paid, the warranty period if the goods are damaged or defective and the availability of spare parts and replacements according to the price and quality of the goods and services that have been determined. This study uses normative juridical by reviewing literature and regulations from legislation by analyzing according to the problems to be studied. The result is that the agreement that has been agreed upon by the parties gets a guarantee or legal certainty because it is binding and must not be violated.